Learning and complex behavior - Donahoe, John W. 1932-; Palmer, David C. 1947-; Dorsel, Vivian Packard (Boston Allyn and Bacon, 1994)
Written from the perspective of selectionist theory, this text presents a theoretically integrated approach to the study of animal learning and human cognition that co-ordinates behavioural research and research in neuroscience. It covers traditional topics such as acquisition and extinction of behaviour, stimulus control and schedules of reinforcement, and also deals with topics of student interest such as perception, memory, problem solving and verbal behaviour. All of these topics are discussed in terms of principles established by experimental analysis at the behavioural and neural levels, and scientific interpretation based on those principles.
I. The Origins of learned behavior --- II. Selection of behavior --- III. Environmental guidance of behavior --- IV. Selection in the experienced learner --- V. Classes of environment-behavior relations --- VI. Attending --- VII. Perceiving environment-environment relations --- VIII. Memory: reminding --- IX. Functioning of the experienced learner --- X. Problem solving --- XI. Verbal behavior --- XII. Remembering.
Includes bibliographical references (pages 365-393) and indexes.
Keywords: Learning, Psychology of; Behaviorism (Psychology); Cognitive psychology; Cognition; Behaviorism; Learning